MOF-derived α-MnSe/C composites as anode materials for Li-ion batteries. Issue 17 (1st December 2019) - Li, Zongyang; Liu, Hongdong; Huang, Jiamu; Zhang, Lei
Abstract: As a member of transition metal chalcogenides (TMCs), α-MnSe is a prospective anode material for lithium-ion batteries (LIBs). However, there are few studies about its application in LIBs. In this work, two unique structures of α-MnSe/carbon nanofiber (α-MnSe/CNF) and α-MnSe/C microspheres were prepared using manganese-based metal organic framework (Mn-BTC) as forerunner that reacted with Se powder at elevated temperature. The MnSe nanoparticles of in-situ formation are uniformly anchored on CNF originated from the organic ligands of Mn-BTC. As a result, α-MnSe/CNF and α-MnSe/C microspheres exhibit excellent lithium storage performance. The α-MnSe/CNF delivers specific capacities of 845.54 mAh g −1 after 100 cycles at 0.1 A g −1 . Even at 1.0 A g −1, it still remains a reversible capacity of 544.6 mAh g −1 after 500 cycles. As for α-MnSe/C microspheres, the corresponding capacities are 784.82 and 516.86 mAh g −1, respectively.